Assessing CSR strategies and Stakeholder Relations in Corporate Banking Sector: A Case of PASHA Bank Azerbaijan - Mammadova, Asli (ADA University, 2019)
Digital transformation means not only changing from traditional banking to a digital sphere, but more than that. It is considered a major transformation in the process of how banks and financial organizations the chance to learn and interact with customers; while at the same time satisfies them. Digital transformation enhances the understanding of digital consumer behavior, likes and dislikes, as well as preferences, which further leads the organizations to become customer-centric rather than product-centric (Peter, 2019). As an effective marketing tool, digital transformation with a particular emphasis on mobile channel can give consumers an access to their balance at anytime and anyplace. In addition, digitization of banking can allow for personalization of marketing offers and personal financial management. Transformation is worthy, while assurance is of utmost importance when it comes to building trust and managing risks (KPMG, 2018). Hence, the question arises on whether the expansion of digitization in banks can preserve business ethics, particularly consumer rights. This is where the human factor comes in. The evolution of PASHA Bank’s CSR strategy also highlights the transformation from CSR activities as a marketing tool (1st Stage) to formation of strategic partnerships with charity institutions (2nd Stage), and finally to value creation for both the society and bank itself.
Keywords: Business; Banks and banking -- Technological innovations.; Banks and banking -- Technological innovations -- Azerbaijan.; Digital banking.; Digital banking -- Azerbaijan.